Analysis of Smart Economy in Increasing UMKM Income through Digital Education in the Northern Coast of Maneron Village, Sepulu District (Case Study of UMKM Actors) - Maruti Djulaeha; Octaviana Arisinta (Global Action and Education for Society, 2025)
Smart Economy is a technology-based approach in managing the economic sector to improve efficiency, productivity, and business competitiveness. In today's digital era, MSMEs are faced with the demand to be able to adapt to technological developments, one of which is through the implementation of Smart Economy. This study aims to analyze the extent to which the implementation of Smart Economy can increase the income of MSME actors in Pesisir Utara, Maneron Village, Sepulu District. This study uses a descriptive qualitative approach with a case study method on five MSME actors who have used digital technology in their business processes. The results of the study show that the implementation of e-commerce and social media has a direct impact on increasing income and expanding the reach of the MSME market. However, there are still obstacles in terms of digital literacy, internet infrastructure, and business assistance. This study recommends continuous digital training, strengthening infrastructure, and multi-party collaboration as strategies to strengthen the Smart Economy in coastal areas.